Los efectos de la hibridación de las fiestas culturales de la parroquia Zumbahua - Toaquiza Manzano, Huáscar Marco (2016)
Traditional festivals are constituted as a fundamental element, because they show the cultural practices of each communities in Ecuador, this festivals. Have an historical, symbolic, and cultural valve. The research emphasizes on the effects about cultural hybridization of the traditional festivals “Tres Reyes Magos” and “Corpus Cristi”, representative expressions at celebrations that communities live. Research identifies transcendental facts for cultural hybridization such as migration, globalization and communication. Processes that have led communities to adopt patterns as lifestyle that became visible in fashion, music, festival and lexicon….